JUAL BELI DENGAN SISTEM DISKON PERSPEKTIF HUKUM EKONOMI SYARIAH DAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 - Dalilatul Baro’ah (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
Sharia also provides clear rules regarding the pillars and conditions of buying and selling. Both refer to the seller, buyer, or subject of a completed commercial and sales contract. The buying and selling marketing strategy is a price reduction system or what we usually call a discount system. It can be found that often the price of the item being discounted is not actually cut. However, the price of a product is raised before a discount is applied. This is called Mark Up. The purpose of this research is to find out the concept of buying and selling with a discount system in sharia economic law and law. The results of this study are to discuss buying and selling with a discount system from the perspective of Islamic economic law and law number 5 of 1999, where there are many discount systems found in society where the price discounts are very attractive. The discount according to sharia is basically permissible if the pillars and conditions in the sale and purchase agreement have been fulfilled. These conditions include that the seller and the buyer have bought and sold willingly and voluntarily, without any coercion and that both parties are competent in carrying out the practice of buying and selling, that is, he is a mulatto. Regarding the object of sale and purchase, it is a sacred and useful item, not unclean or illegitimate, is fully owned, the object of sale and purchase can be handed over, and the amount of payment is known clearly by both parties.